2016
DOI: 10.1002/2016ja022532
|View full text |Cite
|
Sign up to set email alerts
|

Strong ambipolar‐driven ion upflow within the cleft ion fountain during low geomagnetic activity

Abstract: We investigate low‐energy (<10 eV) ion upflows (mainly O+) within the cleft ion fountain (CIF) using conjunctions of the Enhanced Polar Outflow Probe (e‐POP) satellite, the DMSP F16 satellite, the SuperDARN radar, and the Resolute Bay Incoherent Scatter Radar North (RISR‐N). The SEI instrument on board e‐POP enables us to derive ion upflow velocities from the 2‐D images of ion distribution functions with a frame rate of 100 images per second, and with a velocity resolution of the order of 25 m/s. We identify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…The May 2014 event has been previously discussed by Shen et al. (2016), and it was also a large ion upflow event observed by the enhanced Polar Outflow Probe (e‐POP). Both of these events occurred during while the IMF had a northwards component and both were observed using topside modes at RISR‐N.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…The May 2014 event has been previously discussed by Shen et al. (2016), and it was also a large ion upflow event observed by the enhanced Polar Outflow Probe (e‐POP). Both of these events occurred during while the IMF had a northwards component and both were observed using topside modes at RISR‐N.…”
Section: Resultsmentioning
confidence: 67%
“…During these events, RISR-N observed strong temperature enhancements, the SuperDARN backscatter coverage in the vicinity of RISR-N was reasonable, and the convection pattern exhibited dayside reverse convection cells resulting in sunwards flows. The May 2014 event has been previously discussed by Shen et al (2016), and it was also a large ion upflow event observed by the enhanced Polar Outflow Probe (e-POP). Both of these events occurred during while the IMF had a northwards component and both were observed using topside modes at RISR-N.…”
Section: Modeling Joule Heating Events With Ipwmmentioning
confidence: 80%
“…Loranc et al (1991) found 100-3,000 m/s upward ion flows in the high-latitude F-region and associated them with sudden increases in ion temperature due to frictional heating from rapid increases in convection velocity. Shen et al (2016) observed quite time intense low-energy ion upflows in the cleft associated with downward field aligned currents and convection velocity gradients. In the midnight sector, Archer et al (2015), ( 2017) consistently observed ion upflows averaging 150 m/s collocated with perpendicular ion heating within the BCBF regions.…”
Section: Discussionmentioning
confidence: 96%
“…However, to our knowledge, no study has yet documented a statistical relationship between FACs and ion upflow. Despite many statistical and event studies on either ion upflow or FACs (Shen et al, 2016), there is still a knowledge gap regarding the occurrence of ion upflow in relation to FACs during magnetic quiet and disturbed times. Nevertheless, the relationship between FACs and ion upflow is essential for a deeper understanding of magnetosphere‐ionosphere coupling.…”
Section: Introductionmentioning
confidence: 99%